Investigation of the Receiving United States National Disaster Medical System (NDMS) Disaster Medical Assistant Team (DMAT) in Japan: Development of Standard Operation Procedures for Receiving International Medical Teams. (November 2022) - Koido, Yuichi; Kubo, Tatsuhiko; Toyokuni, Yoshiki; Matsuzawa, Yuki; Yano, Yoshiteru; Katsube, Tsukasa
Abstract : Background/Introduction: Japan DMAT and US DMAT have been collaborating in the past to prepare for expected and unexpected disasters in Japan. Japan is predicting overwhelming disasters on Japanese soil soon, which needs efficient and optimum use of resources in medical assistance, including additional support from overseas, particularly from the US. The Japanese government established a large-scale Earthquake/Tsunami Disaster Emergency Response protocol in 2020. However, this protocol does not include any standard operation procedure (SOP) to receive an international medical team. Objectives: Establishing the SOP of receiving medical assistance from US-DMAT based on the WHO International Emergency Team (EMT) initiative. Method/Description: Collaborated with the Office of the Assistant Secretary for Preparedness and Response (ASPR) of the United States Health and Human Services, tabletop exercises assuming that a large-scale earthquake occurred during hosting the 2025 Osaka Expo was conducted online meeting system. Results/Outcomes: Provisional SOP was formed by the Japan research team and ASPR representatives. Even though Japan had several disaster medical assistance collaborations with US DMAT and is well-familiarized with the Classification and Minimum Standards for Emergency Medical Teams, many issues need to be prepared to accept US DMAT. Conclusion: Numerous procedures need to be conducted to receive US DMAT assistance during a large-scale earthquake in Japan. With this SOP, receiving US medical team assistance will be conducted promptly, eventually saving many lives. This SOP can be modified for other international teams' acceptance in Japan. It could reference other countries seeking to have SOPs for receiving international medical team assistance in the near future.